(3YbGFO GdUOhbs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B.. (3GdHGH GdChd aj UaI GYJbGO GdEeGejI aj GdJhMjO bGd (B... (3GYJbGOfG aj GdJhMjO Cf Gddg JYGdi hGMO CMO djS ceKdg TjA bOje de jRd hdG jRGd SejYG HUjQG (B...s
(3BNQgG (B:s
... (3aUd aj GdJbjI bGd GdTjN QVj Gddg Yfg GYJbGOfG aj GdJbjI CfgG hGLHI ef JQcgG cGf HefRdI JQc GdUdGI , hbjd ddUGOb jGHf QShd Gddg EfG fQi aj GdeSLO QLdG (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/274s
(3GdPQjYI (B2/887s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds